How does new-type urbanization promote green development efficiency in China? The mediating role of governments, enterprises, and residents - Haitao Ma; Kewen Wang; Chuanglin Fang (Geography and Sustainability)
New-type urbanization (NTU) is proposed by China to solve unsustainable issues and improve green development efficiency (GDE) during the process of rapid urbanization. However, the impact mechanism of NTU on GDE is unclear. Using panel data of 282 prefecture-level cities in China from 2010 to 2019, we measured NTU and GDE to describe their spatiotemporal pattern and relationship evolution. The fixed effects panel model and mediating effect panel model were further utilized to analyze the benchmark impact, mediating mechanism and spatiotemporal heterogeneity of NTU on GDE. The results showed that NTU improved, with the highest levels observed in the eastern region, while GDE increased with fluctuations, performing better in both the eastern and western regions. With the proportion of double-high cities increasing from 13.83 % to 43.62 %, the NTU-GDE relationship was upgraded. Overall, every 1 % improvement in NTU increased GDE by 0.3111 %, and the enterprise effect, resident effect and government effect played a positive mediating role from high to low. During the later stage of NTU, its impact on GDE strengthened significantly, and the mediating role of governments was optimized. The eastern region was the only region with three positive mediating roles of governments, enterprises and residents. These findings will promote GDE through NTU in China and serve as a valuable reference for sustainable global urbanization.